Pengetahuan Ibu Hamil Tentang Pemberian Zat Besi Di Puskesmas Tanjung Karang - Hairah, Mifanatul; Cahyaningtyas, Dwi Kartika (Research of Service Administration Health and Sains Healthys, 2021)
Pregnant women is a women who is pregnant, is pregnant mother should pay more attention to their health due to pregnancy and childbird very rizky to the health of mother and baby, one important element of nutrition in pregnancy is iron, iron work for the formation of hemoglobin which transports oxygen and nutrients throughout the body tissue and helps the metabolisme to produce energy, if maternal iron deficiency will cause bleeding, impaired fetal growth in the womb to maternal and fetal death. the purpose of this study was to determine the knowledge of pregnant women about the addition of iron to prevent anemia and in particular goal is to identify the knowledge of pregnant women about the addition of iron to prevent anemia based on the caracteristics of age, adecation and work..this research is deskriptif. Research approach used is a cross sectional approach to the measurement or observation research conducted simultaneously at one time.